2012
DOI: 10.1186/1556-276x-7-289
|View full text |Cite
|
Sign up to set email alerts
|

Substrate effects on the strain relaxation in GaN/AlN short-period superlattices

Abstract: We present a comparative study of the strain relaxation of GaN/AlN short-period superlattices (SLs) grown on two different III-nitride substrates introducing different amounts of compensating strain into the films. We grow by plasma-assisted molecular beam epitaxy (0001)-oriented SLs on a GaN buffer deposited on GaN(thick)-on-sapphire template and on AlN(thin)-on-sapphire template. The ex-situ analysis of strain, crack formation, dislocation density, and microstructure of the SL layers has established that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
(35 reference statements)
0
34
0
2
Order By: Relevance
“…However, the drain on the proposed structure of the metal occurs as a result of the reduced electric field strength at the edge of the gate and the drain. Considering the above points, the distance between the gate and recessed metal key parameter in determining the breakdown voltage of the HEMT is improved [24][25][26][27][28]. Apart from it, the breakdown voltage is also influenced by the width of the recessed Table 2.…”
Section: Simulations Results and Discussionmentioning
confidence: 98%
“…However, the drain on the proposed structure of the metal occurs as a result of the reduced electric field strength at the edge of the gate and the drain. Considering the above points, the distance between the gate and recessed metal key parameter in determining the breakdown voltage of the HEMT is improved [24][25][26][27][28]. Apart from it, the breakdown voltage is also influenced by the width of the recessed Table 2.…”
Section: Simulations Results and Discussionmentioning
confidence: 98%
“…This behavior in the SL period can be explained from determination of average parameters. Average lattice parameters in the SL period were calculated from the equations (1)- (6). From these equations, one can see that those SL periods are strongly dependent on the thickness ratio well-barrier and on barrier composition.…”
Section: Discussionmentioning
confidence: 99%
“…In previous works [3][4][5][6], it was shown that at epitaxial growth of nitride structures they relaxed by formation of dislocations and other defects also by changing of well-barrier thicknesses in SL from technological thicknesses. The deformation state, thickness fluctuation and defects in SL negatively affect on the devices performance changing their wavelength, carrier transport and carrier lifetime [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For ion-modified layers, the structural changes can be qualitatively investigated by analyzing the X-ray diffraction curves in the Bragg geometry. In addition, simulation of X-ray diffraction curves can be used for the depth profiles of strain determination [7][8][9]. However, for the ion-modified structures, simulation of XRD spectra is a difficult task with ambiguous solutions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%